ZIARAH SUCI DAN ZIARAH RESMI (Makna Ziarah pada Makam Santri dan Makam Priyayi) - Fikria Najitama (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This article studies the meaning of ziarah which is done by thepeople towards two cemetery in Kebumen, Syekh Anom Sidakarsa’s tomband Adipati Tumenggung Kolopaking’s tomb. Anthrophological approachis functioned as a method to get the belief dimensions, one’s belief, ritualand tradition that is followed by many people. It has been found that thepeople there has some beliefs, the rituals are identical, especially on theprayer and text they are almost the same. In general, the motivation ofthe people is to get barakah and the functions are as a prayer, problemsolver, a hope and a tour.